A comparative study on top-gated and bottom-gated multilayer MoS2 transistors with gate stacked dielectric of Al2O3/HfO2. (13th April 2018) - Zou, Xiao; Xu, Jingping; Huang, Hao; Zhu, Ziqang; Wang, Hongjiu; Li, Borui; Liao, Lei; Fang, Guojia
Abstract: Top-gated and bottom-gated transistors with multilayer MoS2 channel fully encapsulated by stacked Al2 O3 /HfO2 (9 nm/6 nm) were fabricated and comparatively studied. Excellent electrical properties are demonstrated for the TG transistors with high on–off current ratio of 10 8, high field-effect mobility of 10 2 cm 2 V −1 s −1, and low subthreshold swing of 93 mV dec –1 . Also, enhanced reliability has been achieved for the TG transistors with threshold voltage shift of 10 −3 –10 −2 V MV –1 cm –1 after 6 MV cm −1 gate-biased stressing. All improvement for the TG device can be ascribed to the formed device structure and dielectric environment. Degradation of the performance for the BG transistors should be attributed to reduced gate capacitance density and deteriorated interface properties related to vdW gap with a thickness about 0.4 nm. So, the TG transistor with MoS2 channel fully encapsulated by stacked Al2 O3 /HfO2 is a promising way to fabricate high-performance ML MoS2 field-effect transistors for practical electron device applications.